2000
DOI: 10.1055/s-2008-1072339
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Bailey-Dubow Rodding in Children with Osteogenesis Imperfecta

Abstract: We concluded that the use of Bailey-Dubow rods in early childhood can be recommended for the femur, whereas insertion into the tibia or humerus is associated with a considerable complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…Failure of telescoping and subsequent intramedullary migration of the rod have been reported in several clinical series 6,7,[9][10][11][13][14][15][16]20 . A telescopic rod elongates only when the forces generated by proximal and distal fixation points exceed the friction forces between the sleeve and the obturator and between the hardware and the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Failure of telescoping and subsequent intramedullary migration of the rod have been reported in several clinical series 6,7,[9][10][11][13][14][15][16]20 . A telescopic rod elongates only when the forces generated by proximal and distal fixation points exceed the friction forces between the sleeve and the obturator and between the hardware and the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…5). Karbowski et al reported that the tibia has a higher rate of this complication than does the femur and that cutting through by the T-piece occurs more frequently at the distal part of the tibia 16 . We believe that the interlocking pin used with the interlocking telescopic rod, if properly implanted, provides stronger anchorage than does a T-piece.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic efforts are aimed at maximizing mobility and other functional capabilities [4, 6]. Standing and walking can often only be achieved after femora and tibiae have been straightened using intramedullary rods [5, 7, 8]. This treatment approach can be successful, but does not alter the often extreme bone fragility in these patients.…”
Section: Bisphosphonate Therapy In Oimentioning
confidence: 99%
“…The femur is the most common bone that requires surgical correction in OI as a result of fractures and progressive deformities [5,6]. The femoral midshaft appears to be the most common site [7].…”
Section: Introductionmentioning
confidence: 99%